Do horses benefit from provision of shade in hot, sunny weather, and do they prefer it? - Holcomb, K.; Tucker, C.; Stull, C. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
Housing that prevents horses from performing behaviors to maintain their own comfort may have consequences on their performance and interactions with humans. Studies of housing in relation to weather conditions have largely focused on winter environments, with limited mention of hot weather and shade use in summer. We present two studies that examined whether horses benefit from shade and if they would use shade when available during hot, sunny summers in Davis, CA. In each study, physiological measures included rectal temperature (RT), respiration rate (RR), skin temperature (SK), and water consumption. Behavioral measures included foraging, locomotion, and proximity to water. Ambient temperature (Tamb), relative humidity (RH), black globe temperature (TBGT), soil temperature (Tsoil), and solar radiation were recorded. Data were analyzed using Proc Mixed in SAS 9.3. Significance was considered when P < 0.05. To evaluate physiological and behavioral responses to shade, 12 horses were housed individually in either completely shaded (SH) or completely unshaded (SUN) pens, with 5 days of measurement and observation from 1200-1800 h for each treatment using a crossover design. Horses in SUN showed greater RT, RR, and SK, stood near the water in more observations, and consumed more water than horses in SH. The RT was consistently greater in SUN than in SH at all hours, with the largest difference at midday when solar radiation peaked. To quantify the preference of horses for shade, 11 horses were housed individually for 5 to 7 days in pens with half the area shaded and the other half unshaded. Horses were observed in the shade in 7.1% more observations during daylight hours than would be expected by chance. Time of day was a significant factor, as horses were observed more often in the shade at midday, corresponding to peak solar radiation, and in late afternoon following peak Tamb and TBGT. Future research should consider horses with compromised health, very old or young horses, or climates with high humidity and extreme temperatures. Layperson`s paragraph: Given a choice, mature horses showed a preference for using shade under summer conditions. Shade provided significant physiological benefits even with limited use.